Health‐related quality of life trajectories in melanoma patients after electrochemotherapy: real‐world insights from the InspECT register. (1st August 2022) - Campana, L.G.; Quaglino, P.; de Terlizzi, F.; Mascherini, M.; Brizio, M.; Spina, R.; Bertino, G.; Kunte, C.; Odili, J.; Matteucci, P.; MacKenzie Ross, A.; Schepler, H.; et al.
Abstract: Background: Electrochemotherapy (ECT) effectively controls skin metastases from cutaneous melanoma. Objectives: This study aimed to evaluate health‐related quality of life (HRQoL) in melanoma patients pre−/post‐ECT and its effect on treatment outcome. Methods: The analysis included prospective data from the International Network for Sharing Practices of ECT register. Following the Standard Operating Procedures, patients received intravenous or intratumoural bleomycin (15 000 IU/m 2 ; 1000 IU mL/cm 3 ) followed by 100‐microsecond, 1000‐V/cm electric pulses. Endpoints included response (RECIST v3.0), local progression‐free survival (LPFS), toxicity (CTCAE v5.0), and patient‐reported HRQoL at baseline, one, two, four, and 10 months (EuroQol [EQ‐5D‐3L], including 5‐item utility score [EQ‐5D] and visual analogue scale for self‐reported health state [EQ‐VAS]). Comparisons within/between subgroups were made for statistical and minimal important differences (MID). HRQoL scores and clinical covariates were analysed to identify predictors of response in multivariate analysis. Results: Median tumour size was 2 cm. Complete response rate, G3 toxicity, and one‐year LPFS in 378 patients (76% of the melanoma cohort) were 47%, 5%, and 78%, respectively. At baseline, age‐paired HRQoL did not differ from the general European population. Following ECT, both EQ‐5D and EQ‐VAS scores remained within MID boundaries, particularly among complete responders. A subanalysis of the EQ‐5D items revealed a statistically significant deterioration in pain/discomfort and mobility (restored within 4 months), and self‐care and usual activities (throughout the follow‐up) domains. Concomitant checkpoint inhibition correlated with better EQ‐5D and EQ‐VAS trajectories. Baseline EQ‐5D was the exclusive independent predictor for complete response (RR 14.76, P = 0.001). Conclusions: HRQoL of ECT melanoma patients parallels the general population and is preserved in complete responders. Transient deterioration in pain/discomfort and mobility and persistent decline in self‐care and usual activities may warrant targeted support interventions. Combination with checkpoint inhibitors is associated with better QoL outcomes. Baseline HRQoL provides predictive information, which can help identify patients most likely to respond.